Ökonomische Effekte ausländischer Unternehmen in Deutschland - Cora Jungbluth; Eva Rytter Sunesen; Morten May Hansen; Joshua Brown (Wirtschaftsdienst, 2020)
Die Globalisierung ist mit komplexen Wertschöpfungsketten und den Wirtschaftstätigkeiten von Unternehmen verbunden, die von ausländischen Investoren kontrolliert werden. Welche ökonomischen Effekte haben ausländische Unternehmen auf das Bruttoinlandsprodukt und die Beschäftigung in Deutschland? Sie leisten einen Beitrag zur lokalen Wirtschaft, indem sie Arbeitskräfte beschäftigen, Waren und Dienstleistungen von lokalen Lieferanten kaufen und durch Spillover-Effekte die Produktivität lokaler Unternehmen steigern. – – Foreign-owned firms play an important role in global value chains and can positively impact their host economy. A positive net effect should not be taken for granted, though, as new economic activities of foreign-owned firms can crowd out economic activity of local companies. The analysis shows that the overall effect of foreign-owned firms on the German economy is positive. From an economic policy perspective, it would make sense to better communicate the benefits of foreign-owned firms and improve national and international framework conditions for foreign investors while at the same time avoiding a 'race to the bottom' such as unhealthy tax competition.
Keywords: F20; F21; F23; 330